Dilemmas in determinism the prevalence of human personality over the designed environment of Gawad Kalinga-Baseco - Perez, Angelito Rene R. (Quezon City College of Architecture, University of the Philippines Diliman, 2011)
This thesis is, essentially, an analysis of the present condition of a low-cost housing project designed and built by a community development model called Gawad Kalinga (GK) in Baseco, Manila, Philippines. It argues that design for human dwellings can only be imposed to a certain extent; and, contrary to the prescription of architectural determinism, the environment is shaped, albeit forcibly, by the personality of its users. A personality tool based from the Myers-Briggs Type Indicator, contextualized in the vernacular, is administered to beneficiaries, who are consequently grouped according to personality type. Their respective dwelling units then undergo a design audit, documenting how their typical units have developed after the turn-over. Expectations and opinions of the respondents were documented as well via focused group discussion and resource person interviews. On top of these, desk research was referenced to provide further historical data. The findings of the study may be beneficial for Gawad Kalinga and other community development and real estate models in the design and planning of new villages, as the social and behavioral impacts of the designed environment in marginalized communities may be gauged by conducting post occupancy evaluation such as this. As well, since most of the environmental psychology resources are in Western contexts, the study may serve as a useful reference for urban design, housing, and institutional development in the Philippines. further studies are recommended to validate the findings in this research.
Vita.
Thesis (Master of Architecture)--University of the Philippines.